INDEKS KESEHATAN LINGKUNGAN DI WILAYAH KERJA PUSKESMAS BANDARHARJO KOTA SEMARANG - Anggina May Deviar; Budiyono Budiyono; Mursid Rahardjo (Jurnal Kesehatan Masyarakat (Undip), 2016)
The environment is one section that has a major influence on people, especially for health. The prevalence of diarrhea in Bandarharjo Village is 7.44%, and the prevalence of diarrhea Tanjung Mas village is 3.41%, the prevalence of pneumonia in Bandarharjo Village is 3.83%, and the prevalence of pneumonia Tanjung Mas village is 0.90%. In this case, both have similiar conditions in terms of economy, education, and environmental problems that are rob, but they are different conditions of disease . Environmental Health Index is an instrument which is able to describe the environmental health conditions in a region. This study aimed to analyze the differences in environmental health index (EHI) in the rob area the city of Semarang. The method used was observational with cross sectional approach. Data were collected by questionnaire and observation of 200 respondents. Statistical analysis was used the Kolmogorov-Smirnov and Mann-Whitney. The results showed both of EHI in the rob area that are in good categories totaling 59 homes (30%). The average of EHI in Bandarharjo higher than EHI at Tanjung Mas are 0.75 and 0.65 both of them which are still in the bad category. Based on the results of different test EHI value in the both village with α = 0.05 was obtained p-value <0.001. This indicates a significant difference in the value of EHI rob them. With this, we can conclude that rob area have a bad index value where the spread of the disease is also high so that it can be said environmental health index value can describe the incidence of disease in the rob area.